CORN FUTURES MARKET: an investor approach - Sanches, Caroline Manoel de Campos; Lopes, Marcelo Roberto Farah; Cella, Daltro (Revista Interface Tecnológica, 2022)
Agricultural commodities show seasonality (harvest and off-season), where prices fall with excess supply (harvest) and rise with shortages of supply or excess demand (off-season).  Corn was chosen because it is an asset with little liquidity, which made it possible to follow the movement of prices calmly, as there are no sudden movements of purchase and sale as occurs with other assets with greater liquidity.  The objective of this work was to review the derivatives market and perform a hedge and spread simulation in the corn futures market.  The study used qualitative and quantitative methods to make it possible to carry out simulated hedge operations.  The realization of this research proved to be important to understand about the risk-return of the commodities market that this type of operation in variable income presents, and contributes to demystifying the futures market, as any investor and/or speculator can have access to this market.
Keywords: Hedge; Corn; Merchandise